A Case Of Bilateral Manual Eye-Gouging Of A British Soldier. Issue 2 (1st June 2003) - Clare, Gerry; Poole, Tom; Govan, James
Abstract : Peacetime assault-related injuries amongst soldiers are common. Whilst the majority of incidents of assault do not result in permanent physical incapacity, some may be devastating, ruining careers and lives. Here we describe one such injury. There is no national register of such injuries; they may, therefore, be under-reported.